The bristle millipede family Lophoproctidae (Diplopoda, Polyxenida) in the Balkan Peninsula and surroundings - Antić, Dragan; Short, Megan (Biologia Serbica, 2023)
In the present study, we examined a small sample of lophoproctids from the Balkan Peninsula and its surroundings. The millipede family Lophoproctidae is recorded from Serbia and Croatia for the first time, with Lophoproctus coecus Pocock, 1894 and Lophoproctinus (?) inferus (Silvestri, 1903) being involved, respectively. In addition, L. coecus is recorded for the first time from Bulgaria and the entire Balkan Peninsula. Finally, the genus Lophoproctinus Silvestri, 1948 is new to the Balkan fauna. Some remarks and the habitats of the new records are given, as well as taxonomic notes, variations in some specimens and a map with all records of the family in the Balkans and its surroundings.